MODEL PENINGKATAN PEMBELIAN PADA MEDIA BELANJA ONLINE INSTAGRAM MELALUI ORIENTASI BELANJA, KUALITAS WEB, HARGA DAN WORD OF MOUTH COMMUNICATIONS - Moch Zulfa; David Yudhianto (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
This research titled “Enchancement Model of Purchase Decision to Instagram Online ShoppingMedia Through Shopping Orientation, Web Quality, Price, and Word of Mouth Communications.”The development of technology is increasing nowadays, with this technology, it makesconsumers easy to do an online transaction like to buy items or services. This research intendsto test influence of shopping orientation, price against the influence of purchase decision throughword of mouth communication survey to consumer in semarang who do an online purchasetransaction. There are 100 respondets of consumers who live in semarang and do an onlinepurchase transaction with purposive sampling method using path analysis. The result of thisresearch shows that shopping orientation variable (X1), web quality (X2), and price (X3), wordof mouth communications (Y1) are affect to purchase decision variable (Y2), either directly andindirectly through word of mouth communications.Keywods : Shopping Orientation, Web Quality, Price, Word of Mouth Communication,Purchase Decision.